Upaya Meningkatkan Berpikir Kritis Siswa SD Dalam Pembelajaran IPS - Arya Chandra Wiguna; Ilma Siti Salamah; Tin Rustini (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
Current higher order thinking skills need to be instilled in students, especially elementary school students. In the application of critical thinking, there are still many obstacles and problems that make many students less in applying critical thinking in learning. This study aims to determine the teacher's efforts in improving critical thinking skills in elementary students, especially in social studies learning. This qualitative research produces descriptive data by carrying out observations and interviews at one of the elementary schools in the city of Bandung. This study shows that the efforts made by teachers in improving students' critical thinking in social studies learning are giving students a problem and they must solve the problem, besides the use of strategies, methods, models, and learning media also has an effect on increasing students' critical thinking, especially in learning social science.